The Feasibility of Audio-Visual Based Digital Storytelling on the YouTube Channel of Our Fairy Tales as a Learning Media - Nancy Angelia Purba; Restio Sidebang; Kresna Ningsih Manik; Surinah (Universitas Negeri Semarang, 2026)
The development of digital technology has encouraged the use of audiovisual learning media in literary learning in higher education. However, conventional methods still dominate literary learning, so more innovative and interesting media for students are needed. This study aims to analyze the feasibility of audio-visual-based digital storytelling on the